If the points A (1, 2), O (0, 0) and C (a, b) are collinear, then(A) a = b(B) a = 2b(C) 2a = b(D) a = –b

If points A(1, 2), O(0, 0),C (a, b) are collinear then area of triangle

formed by these points must be zero.

$\\A(1, 2)=A(x\textsubscript{1} ,y\textsubscript{1})\\ O(0, 0)=O(x\textsubscript{2} ,y\textsubscript{2})\\ C (a, b)=C(x\textsubscript{3} ,y\textsubscript{3})\\ area of triangle= \frac{1}{2} [x\textsubscript{1}(y\textsubscript{2} - y\textsubscript{3}) + x\textsubscript{2}(y\textsubscript{3} - y\textsubscript{1}) + x\textsubscript{3}(y\textsubscript{1} - y\textsubscript{2})]\\ \Rightarrow \frac{1}{2} [x\textsubscript{1}(y\textsubscript{2} - y\textsubscript{3}) + x\textsubscript{2}(y\textsubscript{3} - y\textsubscript{1}) + x\textsubscript{3}(y\textsubscript{1} - y\textsubscript{2})] = 0\\ \Rightarrow [x\textsubscript{1}(y\textsubscript{2} - y\textsubscript{3}) + x\textsubscript{2}(y\textsubscript{3} - y\textsubscript{1}) + x\textsubscript{3}(y\textsubscript{1} - y\textsubscript{2})] = 0\\ \Rightarrow [1(0 - b) + 0(b - 2) + a(2 - 0)] = 0\\ \Rightarrow [-b + 0 + 2a] = 0\\ \Rightarrow -b + 2a = 0\\ \Rightarrow 2a = b\\$

Hence, option C is correct.